Haematological profile of COVID-19 patients from a centre in Singapore. Issue 1 (1st January 2021) - Long, Valencia Shihuan; Ngiam, Jinghao Nicholas; Chew, Nicholas; Tham, Sai Meng; Lim, Zhen Yu; Li, Tony; Cen, Shuyun; Annadurai, Jayagowtham K.; Thant, Sandi Myo; Tambyah, Paul Anantharajah; Santosa, Amelia; Teo, Winnie Z.Y.; et al.
ABSTRACT: Background: Haematological markers such as absolute lymphopenia have been associated with severe COVID-19 infection. However, in the literature to date, the cohorts described have typically included patients who were moderate to severely unwell with pneumonia and who required intensive care stay. It is uncertain if these markers apply to a population with less severe illness. We sought to describe the haematological profile of patients with mild disease with COVID-19 admitted to a single centre in Singapore. Methods: We examined 554 consecutive PCR positive SARS-COV-2 patients admitted to a single tertiary healthcare institution from Feb 2020 to April 2020. In all patients a full blood count was obtained within 24 h of presentation. Results: Patients with pneumonia had higher neutrophil percentages (66.5 ± 11.6 vs 55.2 ± 12.6%, p  < 0.001), lower absolute lymphocyte count (1.5 ± 1.1 vs 1.9 ± 2.1 x109/L, p  < 0.011) and absolute eosinophil count (0.2 ± 0.9 vs 0.7 ± 1.8 × 109/L, p  = 0.002). Platelet counts (210 ± 56 vs 230 ± 61, p  = 0.020) were slightly lower in the group with pneumonia. We did not demonstrate significant differences in the neutrophil-lymphocyte ratio, monocyte-lymphocyte ratio and platelet-lymphocyte ratio in patients with or without pneumonia. Sixty-eight patients (12.3%) had peripheral eosinophilia. This was more common in migrant workers living in dormitories. Conclusion: Neutrophilia and lymphopenia were found to be markers associated with severe COVID-19 illness. We did not find that combined haematological parameters: neutrophil-lymphocyte ratio, monocyte-lymphocyte ratio and platelet-lymphocyte ratio, had any association with disease severity in our cohort of patients with mild-moderate disease. Migrant workers living in dormitories had eosinophilia which may reflect concurrent chronic parasitic infection.